The putative K+ channel subunit AtKCO3 forms stable dimers in Arabidopsis - Rocchetti, Alessandra; Sharma, Tripti; Wulfetange, Camilla; Scholz-Starke, Joachim; Grippa, Alexandra; Carpaneto, Armando; Dreyer, Ingo; Vitale, Alessandro; Czempinski, Katrin; Pedrazzini, Emanuela (Frontiers in Plant Science, 2012)
The permeation pore of K+ channels is formed by four copies of the pore domain. AtKCO3 is the only putative voltage-independent K+ channel subunit of Arabidopsis thaliana with a single pore domain. KCO3-like proteins recently emerged in evolution and, to date, have been found only in the genus Arabidopsis (A. thaliana and A. lyrata). We show that the absence of KCO3 does not cause marked changes in growth under various conditions. Only under osmotic stress we observed reduced root growth of the kco3-1 null-allele line. This phenotype was complemented by expressing a KCO3 mutant with an inactive pore, indicating that the function of KCO3 under osmotic stress does not depend on its direct ability to transport ions. Constitutively overexpressed AtKCO3 or AtKCO3::GFP are efficiently sorted to the tonoplast indicating that the protein is approved by the endoplasmic reticulum quality control. However, vacuoles isolated from transgenic plants do not have significant alterations in current density. Consistently, both AtKCO3 and AtKCO3::GFP are detected as homodimers upon velocity gradient centrifugation, an assembly state that would not allow for activity. We conclude that if AtKCO3 ever functions as a K+ channel, active tetramers are held by particularly weak interactions, are formed only in unknown specific conditions and may require partner proteins.